Induction of zincophore pseudopaline secretion by Cr(VI) and intracellular formation of granules from nanocrystal aggregation by Cr(III) in Pseudomonas aeruginosa. (1st December 2022) - Gong, Beini; Tan, Zewen; Yang, Xiuyue; Liang, Lingling; Wu, Pingxiao; Li, Yongtao
Abstract: When microorganisms are challenged with toxic metals, intracellular granules are commonly observed, however, the exact nature of these granules is poorly understood. Here we show that when Pseudomonas aeruginosa CCTCC AB93066 were exposed to Cr(VI), Cr can enter the cell in the form of both Cr(VI) and Cr(III), and intracellular granules of several hundred nanometers were formed in the nucleoid region and were built up by aggregation of nanocrystals. We suggested that these nanocrystals are organic crystals. Transcriptomic profiles and liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis indicated that pseudopaline (a metallophore that can complex with Zn 2+ ) production and pseudopaline-Zn 2+ import into bacterial cells were enhanced upon Cr(VI) exposure. It was proposed that pseudopaline can scavenge Zn 2+ which is essential for transcription alteration and DNA repair. Excessive pseudopaline might precipitate as nanospheres in the nuclear region that are further agglomerated by Cr(III) to form larger granules. During this process, Cr(III) is sequestered and immobilized. Hence we revealed pseudopaline production and zinc acquisition is crucial for alleviation of Cr(VI) toxicity and intracellular granules are composed of organic nanospheres which are aggregated by Cr(III). Graphical abstract: Image 1 Highlights: Cr can enter the cell in the form of both Cr(VI) and Cr(III). Intracellular granules of several hundred nanometers were formed upon Cr(VI) stress. Intracellular granules are composed of small nanospheres that are aggregated by Cr(III). Pseudopaline production and pseudopaline-Zn 2+ import into cells were enhanced by Cr(VI).